Children from Siri's Marriage as Heirs in Review of Civil Law and Islamic Law - Puruhita, Prasetyawati; Roynita, Windy (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Siri marriages are marriages that do not record their marital status to officials. Siri marriage has a number of detrimental effects on family formation, one of which is the lack of legal certainty in the distribution of inheritance. The author aims to determine the position, rights, and impacts of siri marriage for children of siri marriage as heirs in terms of civil law and Islamic law. The results showed that children from unregistered marriages could have civil ties with both parents and get their full rights if they received recognition from both parents. Meanwhile, Islamic law considers Siris marriage valid because it fulfills the conditions and harmony so that the child has the right to inherit in accordance with applicable regulations.